2023
DOI: 10.1001/jamasurg.2023.3352
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Regret and Satisfaction With Decision Following Gender-Affirming Mastectomy

Lauren Bruce,
Alexander N. Khouri,
Andrew Bolze
et al.

Abstract: ImportanceThere has been increasing legislative interest in regulating gender-affirming surgery, in part due to the concern about decisional regret. The regret rate following gender-affirming surgery is thought to be approximately 1%; however, previous studies relied heavily on ad hoc instruments.ObjectiveTo evaluate long-term decisional regret and satisfaction with decision using validated instruments following gender-affirming mastectomy.Design, Setting, and ParticipantsFor this cross-sectional study, a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[45][46][47] Today, surgeons at UMCGSP have realized many of the early research goals of the CGSP, publishing long-term studies which take advantage of the program's extensive experience providing gender-affirming surgeries. 48 Additionally, the program has dedicated itself to conducting high-quality, prospective studies of patient-reported outcomes in gender-affirming surgery. 38 Beyond surgical outcomes themselves, new work by surgeons at the UMCGSP focuses on accessibility and patient experiences of gender-affirming care.…”
Section: Improvement Of Care Through Gender-affirming Researchmentioning
confidence: 99%
“…[45][46][47] Today, surgeons at UMCGSP have realized many of the early research goals of the CGSP, publishing long-term studies which take advantage of the program's extensive experience providing gender-affirming surgeries. 48 Additionally, the program has dedicated itself to conducting high-quality, prospective studies of patient-reported outcomes in gender-affirming surgery. 38 Beyond surgical outcomes themselves, new work by surgeons at the UMCGSP focuses on accessibility and patient experiences of gender-affirming care.…”
Section: Improvement Of Care Through Gender-affirming Researchmentioning
confidence: 99%
“…The overall rates of detransition and regret in people who began medical transition as children are largely unknown; there are no large-scale studies with long-term follow-up on this cohort (Cohn, 2023 ; MacKinnon et al, 2023 ). Studies describing low rates of regret (i.e., 1–2%) focused primarily on people who transitioned as mature adults and/or are from an era when people had to undergo rigorous psychological screening to be eligible for hormonal therapy and surgery (Bruce et al, 2023 ; Dhejne et al, 2014 ; Wiepjes et al, 2018 ). Moreover, they frequently used narrow definitions of regret such as the application to have birth sex reinstated as legal sex (Dhejne et al, 2014 ) or request for surgical reversal, to the extent possible (Narayan et al, 2021 ).…”
Section: Reversibility Of Puberty Blockersmentioning
confidence: 99%
“…These surgeries are often combined with abdominal and/or chest tumescent liposuction. Rates of postoperative regret after these surgical interventions remain low [25 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%